The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2147/ca.s9665
|View full text |Cite
|
Sign up to set email alerts
|

An audit of orthopedic operation notes: what are we missing?

Abstract: Abstract:The importance of complete and legible operation notes is indisputable. Orthopedic operation notes at the author's institution were audited against guidelines regarding content and legibility. Although of generally good standard it was found that in some cases important information was being missed and that a high proportion of notes had sections that were deemed illegible. A computerized proforma for writing notes has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Audits from Nigeria and other part of Africa have demonstrated similar, and in some instances, poorer results [7][8][9] . Those from developed countries however showed marginally better results 1,10 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Audits from Nigeria and other part of Africa have demonstrated similar, and in some instances, poorer results [7][8][9] . Those from developed countries however showed marginally better results 1,10 .…”
Section: Discussionmentioning
confidence: 92%
“…Operative findings and post-operative plans contained in the notes do not onlyserve as a vital means of communication between health professionals, but are also the only legal record of an operation 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Well-written notes carry great importance in patient care, as they directly impact the follow-up care. The sole account of events occurring during surgery are operative notes [6]. Documentation is pivotal in surgery as circumstances may vary every second.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 20% of the notes had illegible parts, similar to findings in other studies. 10,13 Legibility of signatures can be improved by the use of name stamps.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 20% of the notes had illegible parts, similar to findings in other studies. 10,13 Legibility of signatures can be improved by the use of name stamps. 14 Although all our surgeons found that handwritten notes are easier and less time consuming, computerized notes avoid illegibility and help in medicolegal defence.…”
Section: Discussionmentioning
confidence: 99%